Establishing predictive validity of English exit test: students' EET performance and academic achievement / Faizah Mohamad …[et al.] - Mohamad, Faizah; Abdullah, Normah; Ahmad Buhari, Turisiana; Mat Daud, Nor Shidrah; Ramlan, Zarina Suriya; Ai, Teoh Swee (Universiti Teknologi MARA, 2020)
Graduating students of UiTM are required to sit for English Exit Test (EET) whose objective is to gauge students’ English proficiency level and their readiness for the workplace. Since the test is administered before students finish their studies, it is important to examine if EET has a predictive validity in determining the academic performance of UiTM students. We use the students’ CGPA (Cumulative Grade Point Average) to gauge their academic performance and English language proficiency since English is used as a medium of instruction at UiTM. A four-part predictive validity study was conducted on the relationship between students’ EET performance and academic achievement. A sample of 1,436 students’ EET results and CGPA from various faculties were analysed based on the results from four semesters which were 2016/2, 2016/4, 2017/2 and 2017/4. The relationship among the scores were summarised with correlation coefficients and a series of one-way ANOVA tests were run to see if there were any significant mean differences in the scores based on faculties in a span of two years. The findings revealed that there were positive correlations between students’ EET results and their CGPA. Thus, it can be concluded that EET has the predictive validity for students’ academic achievement which is the CGPA. The present study also found that EET can be considered a good test as the results of EET could differentiate good students from weak ones. This was determined by running a series of One-way ANOVA tests. The results revealed that faculties whose students had high English proficiency level scored better in EET than those whose students who had low English proficiency level. Therefore, the findings indicate that EET has a potential in differentiating high English proficient students from low English proficient students for their language readiness in the workplace.